Aspectos do uso de álcool entre alunos iniciando curso naUFMG - Flavia Antunes Caldeira Silva e Calaca (2006)
The objective of this study was to describe aspects of alcohol use and its prevalence among students at UFMG. A descriptive study with a randomly and representative sample of university students was done for courses in all eight areas of learning at UFMG. The instrument used was an anonymous self-completed questionnaire consisting of questionsas: age of alcohol experimentation, ingestion frequency, quantity and kind of alcoholic beverages, most frequent location and partners, occurrence of binge drinking, drunkenness and its consequences. The data were collected in 2004 from a total of 375 university students between 18 and 25 years of age, 59,2% male and 40,8% female. Results indicatedthat 91,5% of them have already drank alcohol, with equal prevalence of lifetime alcohol use for male and female. The average age for alcohol experimentation was at 14,6 years of age, with no gender differences. Most of students drank alcohol for the first time in their lives, in their own houses, with their friends and relatives. The percentage of students whoreported drinking in the month before the survey was near to 70%, which ones 26,3% reported moderated or heavy drinking. Binge drinking was observed in 28,4% and problem drinking, in 13,5%; both drinking patterns predominated at male students. Beer was the most frequently consumed kind of alcoholic drinks. Bars, discos and stadiums were students favorite locations to alcohol consumption and their friends and classmates were their main partners. Most of them have already been drunk. The most common reported consequence of drunkenness was missing classes, day of work or another important commitment, followed by driving a car and having unprotected sex. It is concluded that a significant percentage of university students engage in dangerousdrinking practices such as heavy drinking, binge drinking and problem drinking. Gender, social status, living arrangement, religion, tobacco use and age of alcohol experimentation have been associated to larger quantities and frequency of alcohol consumption. Furtherstudies are necessary for deeper comprehension about alcohol use among young people, such as knowing their motivation, allowing for better understanding of youths behavior and contributing for effective interventions to prevent or reduce alcohol related risks and consequences.